Bioindicadores de solo cultivado com pinhão-manso submetido a aplicações de água residuária de suínos (ARS) - Pinto, Luana Patricia (2019)
Agricultural production in the West of Paraná is one of the most important in Brazil, combining highly productive animal and vegetable production, as well as exportation of commodities such as soybean and pork. Thus, the constant monitoring and improvement of soil management and quality is increasing. The utilization of wastewater as a fertigation compound is an important alternative for its reuse, being environmentally correct, preventing environmental damage, improving production chain costs, and, mainly, allowing the agricultural producer to recycle soil nutrients. However, there is a need for adequacy and measurement of this recycling dynamics and, for that, assessment of the soil microbial community and its attributes contributes significantly to identify which nutrient changes, since they correspond to the last stage of organic decomposition in soil. In this context, the aim of this study was to define, through microbiological attributes such as density, diversity, and metabolic activity of the soil microbiota, an adequate dosage of AR. In addition, the goal was verify the changes in the microbial community for possible nutrient management parameters in soil and their capacity to support the organic load of these types of residue. The soil class was Red Latosol of the Western region of Paraná, municipality of Palotina, cultivated for 12 years with Jatropha sp., submitted to biannual adubation with swine wastewater (ARS). The experimental design was a randomized block with six treatments and four repetitions with different doses of AR (0, 40, 80, 120, 160, and 200 m³ ha-1), three applications were carried out during 2018. The microbiological attributes of the soil were: counting of bacterial colony forming units (UFC), bacterial morphological typing, microbial biomass carbon (CBM), soil RB (RBS), metabolic quotient (qCO2), microbial quotient (qMIC), and enzymatic activity by FDA methodology. Changes were detected in the profile and functional properties of the microbiological community of soils submitted to ARS. In general, up to the dose of 160 m³ ha-1, CBM, qMIC, and FDA shows increasing values, RBS values change, but discretely while qCO2 showed high environmental stress at dose 200 m³ ha-1. This fact was reinforced by the Shannon and dominances indices, where it was observed a reduction of H’ in the dose 200 m³ ha-1. The profile of the values of bacterial density, diversity and enzymatic functionality obtained for the different samplings during a chosen period along the process of successive applications of ARS, showed that the introduction of new individuals and that these reinforced the groups of soil resilient. The values of qCO2 were able to reveal that the structural alteration promoted by the applications of the ARS, still not harming the metabolic activities, at least not for the functional groups involved in the activities of decomposition and conversion of carbon. The microbiological attributes indicate that the ideal tested ARS dose for use as agricultural fertilizer is 110 m³ ha-1; however, positive agronomic gains with ecological maintenance were achieved in other concentrations up to 160 m³ ha-1, which is the limiting dose for soil support capacity. The values obtained during the samplings indicate that, over time, the soils submitted to the most adequate dose tend to establish a new profile, rebalancing the metabolic activities of the community. It is suggested, therefore, that these studies be extrapolated and continuously applied in other types of soils and crops, so that it is inserted in agronomic recommendations for plant production.